Effect of a Novel Ergonomic Sheath on Dental Device-Related Muscle Work, Fatigue and Comfort—A Pilot Clinical Study - Dang, Steven; Wink, Cherie; Yang, Susan Meishan; Lin, Kairong; Takesh, Thair; Habib, Ali A.; Wilder-Smith, Petra (Dentistry journal, 2024)
Background: Dental instrumentation with hand-held devices is associated with discomfort, fatigue and musculoskeletal diseases or repetitive stress injuries. The goal of this in vivo study was to determine the effect of an ergonomic handle sheath on muscle work, comfort and fatigue associated with (a) piezoelectric scaling by hygienists with and without musculoskeletal disorders (MSDs), and (b) dental cavity preparation by healthy dentists using a dental micromotor. Materials and Methods: Two groups of ten hygienists each tested the piezoelectric scaler. Hygienists in Group 1 had no MSDs, while those in Group 2 had been diagnosed with MSDs. Additionally, ten dentists with no MSDs used a dental micromotor to prepare four standardized cavities. Time-based work in four muscles, comfort and fatigue were recorded in the presence and absence of an add-on soft, insulating handle sheath. Data were analyzed using a repeated measures analysis of variance model with Tukey’s post-hoc test. Results: Comfort, fatigue and muscle work were significantly better for both devices when the sheath was used. While hygienists with MSDs used more muscle work to complete the set scaling task, and the sheath-related reduction in work was somewhat greater, these MSD-related differences did not quite reach significance. Conclusions: The results of this pilot study show that the ergonomic performance of an ultrasonic scaler and a dental micromotor may be improved by the use of an ergonomic handle sheath.